Yield, Produce Quality and Soil Health under Vegetable Cropping Systems as Influenced by Integrated Nutrient Management in Mid-hill Zone of Himachal Pradesh - Parmar, D.K. (Journal of the Indian Society of Soil Science, 2014)
Average yield of vegetables in Himachal Pradesh is low and unbalanced fertilizer use is considered one of the major constraints responsible for the same. There is a need to increase on-farm productivity and profitability through appropriate production techniques. On-farm experiments were carried out during 2006-07 and 2007-08 to study the effect of integrated nutrient management on the yield and quality of marketable produce under frenchbean (Phaselous vulgaris L.)–frenchbean-cauliflower (Brassica oleracea var. brotytis) and cauliflower-cauliflower-pea (Pisum sativum) systems and on the soil properties. Integrated nutrient management (100% NPKB + FYM) increased yields, produce quality and net returns of cropping systems. There was no effect of different treatments on soil pH. However, soil organic carbon was improved in the organic manure treatment (20 t FYM ha-1). Integrated nutrient management (100% NPKB + FYM) increased the availability of N, P, K and B over other treatments. Cauliflower-cauliflower-pea was most remunerative production system followed by frenchbean-frenchbean-cauliflower system, and the former can be recommended for mid-hill zone of Himachal Pradesh.